Protocolos de bioseguridad aplicados al diseño, producción y comercialización de la panadería Londres de la Ciudad de Riobamba - Ramírez Inca, Elida Katerin (2021)
Panadería Londres (London Bakery) is a company in Riobamba which offers to the citizens bakery, biscuit, and pastry products. The objective of this research project is to develop a biosecurity protocol applied to the design, production and commercialization. An initial diagnosis of the processes with the help of a checklist based on in the requirements of the ARCSA-DE-067-2015-GGG resolution, explained by the National Agency of Regulation, Control and Sanitary Surveillance (ARCSA because of its acronym in Spanish) 2015 was developed. Through the flow diagram, the activities were described based on the Hazard Analysis Plan and Critical Control Points (HACCP) development, in which the analysis of the physical, chemical, and biological agents detected in the process is exposed, this document describes the control parameters, monitoring system and corrective actions for the purchasing processes, verification, and proved analysis of raw materials and resources, MP. e I storage and leavening in the production process, considering critical control points (CCP). A final diagnosis was carried out, after this diagnosis the results were: 82.8% (106 items) it fulfils and 17.2% (22 items) it does not fulfil. After the documentation, general biosecurity protocol measures were developed, they include a biosafety procedure against COVID-19, it guarantees the control, reduction and elimination of contagion risks to employees as well as to external customers, contamination of surfaces and products.